The First World Energies Forum—Current and Future Energy Issues 2020
DOI: 10.3390/wef-06921
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conversion of Pine Wood and Kinetic Analysis under Oxidative and Non-Oxidative Environments at Low Heating Rate

Abstract: Atmosphere is one of the most significant factors in the thermal decomposition of biomass. In domestic or industrial biomass boilers, ambient oxygen concentration varies through time, which means that the reaction will change from pyrolysis to combustion. In this way, to analyze and compare each thermochemical conversion process, a simple analytical method, the non-isothermal thermogravimetric analysis, is carried out under oxidative (air) and non-oxidative (argon) environments at 10 °C/min and as a function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The result showed that wood decomposes in two stages. The first stage occurred at 250-390 • C, while the second one was at 390-612 • C. The Ea for these stages were 190 and 117 kJ × mol −1 , respectively [64]. Nevertheless, despite the differences in the observed values, and approaches, the results suggest relatively suitable predictions of conversion in these works.…”
Section: Peat Thermal Decomposition Kinetics By Coats-redfernmentioning
confidence: 76%
See 1 more Smart Citation
“…The result showed that wood decomposes in two stages. The first stage occurred at 250-390 • C, while the second one was at 390-612 • C. The Ea for these stages were 190 and 117 kJ × mol −1 , respectively [64]. Nevertheless, despite the differences in the observed values, and approaches, the results suggest relatively suitable predictions of conversion in these works.…”
Section: Peat Thermal Decomposition Kinetics By Coats-redfernmentioning
confidence: 76%
“…Similarly, it is with wood. For example, Fraga et al [64] analyzed the decomposition of wood using the CR method considering only a first-order reaction model (n = 1). The result showed that wood decomposes in two stages.…”
Section: Peat Thermal Decomposition Kinetics By Coats-redfernmentioning
confidence: 99%
“…In support of the reactivity data, the ignition and combustion indices were calculated for all samples to provide a more accurate measure of the conversion over time and temperature. According to Fraga et al ( 2020b ), the ignition and combustion indices are defined in Eq. 1 and Eq.…”
Section: Methodsmentioning
confidence: 99%
“…According to this model, the kinetic parameters can be determined by the equation presented in Table 4 and neglecting the term 2RT/E, which can be considered much lower than one. The value for A is then determined from the interception of the plot indicated in Table 4 [153], with the possibility to make this analysis at different stages of the conversion process. Otherwise, to complete the determination of the kinetic parameters A and f (α), usually the Kissinger or compensation factor methods and master plots methods have been used to obtain both parameters, respectively [82].…”
Section: Model-name Of Functions F(α) G(α)mentioning
confidence: 99%